AB0529 Long-Term Glucocorticoid Monotherapy Can Lead To Remission in Japanese Patients with Polymyalgia Rheumatica without Notable Adverse Effects. (15th July 2016) - Aoki, A.; Senuma, A.; Osada, A.; Nagaoka, S.
Abstract : Background: Polymyalgia rheumatica (PMR) is a common inflammatory condition of elderly persons. Clinical symptoms are improved by low-dose glucocorticoids (GCs). However, most patients require long-term GC therapy, because relapses are common. The recent recommendations for the management of PMR 1) suggested early introduction of methotrexate (MTX) in addition to GCs in patients with a relapse, and/or without a significant response to GC, or experiencing GC-related adverse events. Objectives: The aim of this study was to evaluate the duration of GC monotherapy until remission of PMR patients, and the adverse events of long-term GC treatment. Methods: We conducted a retrospective study of 29 PMR patients who had achieved remission in 3 hospitals in Japan. All patients met EULAR/ACR classification criteria. None of the patients had clinical symptoms or signs of giant cell arteritis. Patients who had been treated with methotrexate in addition to GCs were excluded. Remission was defined as the absence of symptoms and normal levels of Erythrocyte sedimentation rate (ESR) or C-reactive protein (CRP) after the discontinuation of GC. Treatments to prevent GC related adverse event, especially osteoporosis, were left up to each physicians. Results: 20 (69%) were women. The mean (SD) age at the diagnosis was 75.7 (8.14) (range 61–90) years. The median and mean (SD) of initial prednisolone (PSL) dose was 15 and 13.1 (4.15) mg daily. The median duration of GC treatment until remission was 21 months (range 7–88). Three patients achieved remission after longer than 5 years of GC treatment (66, 69, and 88 months)(Figure ). For analysis, patients were divided into 2 groups; those who achieved remission within 24 months (early remission group; 17) and those who required GC treatment for more than 25 months (long treatment group; 12). A comparison of the 2 groups was done. No difference was observed in clinical features and laboratory data at diagnosis. Furthermore, there was no significant difference in the starting dose of GCs or GCs tapering speed. Most female patients received vitamin D and/or bisphosphonate. Serious GC adverse events, such as osteoporosis associated fractures, and infections, were rare, and the frequencies of adverse events did not differ between the 2 groups. Conclusions: Most patients have achieved a remission within two years. However, some patients required longer-term treatment. The risk factors for prolonged therapy were reported; female sex, elevated ESR, and peripheral inflammatory arthritis. In this study, any clinical factors at diagnosis were not associated with the duration of PSL treatment until remission. Our results indicate that low-dose GC therapy might be safer than was previously reported, as long as efforts are made to prevent GC-related adverse events. The rate of MTX adverse events in elderly is not low. Further studies are necessary to determine the risk and benefit of GC monotherapy References: Dejaco C, et al. 2015 recommendation for the management of polymyalgia rheumatica: Eueopean League Agaist Rheumatism/American College of Rheumatology collaborative initiative. aNN Rheum Dis 2015;74;1799–1807. Disclosure of Interest: None declared